An unusual case report of chlorpheniramine-induced severe thrombocytopenia - Hariri, D. Bassem Al; Alharafsheh, Ahmad Eid Nazzal; Jamal, Sheikh W.; Alhariri, Joudi; Illahi, Memon Noor; Mohamedali, Mohamed Gaafar (International Journal Of Community Medicine And Public Health, 2026)
A rare but fatal illness is drug-induced thrombocytopenia (DITP). Severe thrombocytopenia is not frequently linked to antihistamines, especially first-generation H1 blockers like chlorpheniramine. We describe a rare instance of a 31-year-old man who used chlorpheniramine for rhinitis and thereafter got severe thrombocytopenia (platelet count=0×109/L). The patient had subcutaneous petechiae, bilateral conjunctival hemorrhage, and bleeding gums. Other causes were ruled out by laboratory tests, such as bone marrow analysis and peripheral blood smears. After receiving intravenous immunoglobulin (IVIG) and corticosteroids, the patient’s platelet counts gradually recovered. This instance emphasizes how crucial it is to identify DITP as a side effect of chlorpheniramine so that early diagnosis and treatment may be carried out.